Reform of economic evaluation of medicines in Spain: proposals from the Advisory Committee for Pharmaceutical Financing - Marta Trapero-Bertran; Jaume Puig-Junoy; Emilio J. Alegre-del-Rey; Ana Clopés; Félix Lobo; Ana Ortega (Gaceta Sanitaria)
This paper describes the reforms recommended by the Advisory Committee on the Financing of Pharmaceuticals (CAPF) for the National Health System (NHS) of Spain from 2019 to 2024 for the drug pricing and reimbursement process, to integrate economic evaluations and improve efficiency and sustainability. The CAPF has proposed a three-phase reform of the economic evaluation (EE) and budget impact analysis (BIA) processes. The first phase involves the mandatory submission of EE and BIA by applicants for new drugs. The second phase involves the assessment of these submissions, coordinated by the Directorate-General for Pharmaceuticals. The third phase focuses on the application of these assessments to decision-making on drug positioning, pricing and financing. The CAPF's recommendations emphasise improved regulation, transparency and the development of methodological guidelines for economic evaluations. These proposals include a dynamic appraisal system and the creation of official NHS guidance on EE and BIA. The process is designed to ensure compliance with established criteria and to incorporate efficiency into decision-making. The initiatives of the CAPF aim to make progress towards the integration of efficiency in Spanish pharmaceutical policy seeking to improve the methodological quality and transparency of economic evaluations, ultimately contributing to more informed decision-making and sustainable healthcare practices. Resumen: Este artículo describe las reformas recomendadas por el Comité Asesor para la Financiación de la Prestación Farmacéutica (CAPF) del Sistema Nacional de Salud (SNS) de España entre 2019 y 2024 en el proceso de fijación de precios y reembolso de medicamentos, con el fin de integrar evaluaciones económicas y mejorar la eficiencia y la sostenibilidad. El CAPF ha propuesto una reforma en tres fases de los procesos de evaluación económica (EE) y análisis de impacto presupuestario (AIP). La primera fase implica la presentación obligatoria de EE y AIP por parte de los solicitantes de nuevos medicamentos. La segunda fase implica la evaluación de estas presentaciones, coordinada por la Dirección General de Farmacia. La tercera fase se centra en la aplicación de estas evaluaciones en la toma de decisiones sobre el posicionamiento, la fijación de precios y la financiación de los medicamentos. Las recomendaciones del CAPF destacan la mejora de la regulación, la transparencia y el desarrollo de directrices metodológicas para las EE. Estas propuestas incluyen un sistema de evaluación dinámico y la creación de una guía oficial del SNS sobre EE y AIP. El proceso está diseñado para garantizar el cumplimiento de los criterios establecidos e incorporar la eficiencia en la toma de decisiones. Las propuestas del CAPF tienen como objetivo avanzar hacia la integración de la eficiencia en la política farmacéutica española y buscan mejorar la calidad metodológica y la transparencia de las EE, contribuyendo en última instancia a una toma de decisiones más informada y a prácticas de atención sanitaria sostenibles.